Localization of Angina Related Artery by Admission ECG in Unstable Angina and NSTEMI Patients - Arpan P. Desai; Rajeev Bhagarhatta (Journal of Hypertension and Cardiology, 2016)
Objective: To find out the diagnostic accuracy of admission ECG against coronary angiography (CAG) to predict the ARA in patients with USAP /NSTEMI. Background: In USAP even though multiple active plaques are documented, one critical lesion would be responsible for the index episode of angina. Contrary to STEMI there is no standard methodology to identify the Angina related artery (ARA) in USAP.Therefore we plan to determine whether admission ECG could predict the ARA in patients with USAP/NSTEMI. Patients and Methods: 250 eligible patients with USAP/NSTEMI undergoing coronary angiography were enrolled in the study. After locating the ARA , the patient’s admission ECG was compared with CAG finding to study whether it has any predictive value for identifying ARA. Results: Sensitivity of the admission ECG for LAD as ARA was 73.6%, Specificity was 93.5%, PPV was 90%, NPV was 81.8%, +LR 10.4, Posterior probability 0.89, -LR 0.29, Posttest odds 0.22. Similarly for RCA and LCx ,Sensitivity was 63.1%, Specificity was 93.7%, PPV was 90.5%, NPV was 72.7%, +LR 9, Posterior Probability 0.89, -LR 0.35, Posttest odds 0.33. For the LM and TVD, Sensitivity was 66.6%, Specificity was 98.5%, PPV was 91.4%, and NPV was 92.5%, +LR 33, Posterior Probability 0.89, -LR 0.33, Posttest odds 0.08. Conclusion: With high +LR, Admission ECG is moderately sensitive and highly specific for detecting culprit artery.
Keywords: Angina Related Artery